A Large-Scale Quantitative Survey of the German Geocaching Community in 2007. (26th June 2014) - Telaar, Daniel; Krüger, Antonio; Schöning, Johannes
Abstract : We present a large-scale quantitative contextual survey of the geocaching community in Germany, one of the world's largest geocaching communities. We investigate the features, attitudes, interests, and motivations that characterise the German geocachers. Two anonymous surveys have been carried out on this issue in the year 2007. We conducted a large-scale qualitative general study based on web questionnaires and a more targeted study, which aimed at a comprehensive amount of revealed geocaches of a certain region. With sample sizes ofn = 1982 (study 1: general study) andn = 310 (study 2: regional study) we provide a representative basis to ground previous qualitative research in this domain. In addition, we investigated the usage of technology in combination with traditional paper-based media by the geocachers. This knowledge can be used to reflect on past and future trends within the geocaching community.